ESTUDO DO ACIONAMENTO PNEUMÁTICO DE UMA BANCADA PARA CONCURSO DE PÓRTICOS - Santos, Felipe L. d.; Nascimento, Karl B. X. d.; Weber, Samantha I.; Ritter, Douglas; Valdieiro, Antonio C.; Rasia, Luiz A. (Salão do Conhecimento, 2013)
Resumo